Innovation in Sustainability Communication - A proposal towards a holistic communication framework - Beatriz Fidelis Thomaz Maya (2021)
This work has two main objectives. The first objective of this study is to map out the best practices used to implement projects that communicate sustainability values and activities in a selected number of MNCs considered 'sustainable' by the Corporate Knights Global 100 Index, according to the following dimensions: target audience, content, process and efficacy measurement; The second objective of the study is to propose a holistic framework design to standardize the process of communicating sustainability activities and values, test the proposed framework, and iterate if needed. This study is developed through a mixed methodology and is divided into two phases. Phase A comprises two steps (data collection and interviews) to propose a framework. Phase B covers the stage of iteration and correction of the proposed framework (through new interviews). The study successfully reaches its goal of developing a sustainability communication framework (SCF) to be used by companies that aim to structure their communication process. The research questions that aim to study and structure the processes used by the Global 100 Index to communicate sustainability actions and values to their various stakeholders - by defining their main objectives, target audiences, channels, and contents, and how they measure their overall communication efficacy - are successfully answered and allow for the development of the SCF to be anchored in experiences of MNCs and sustained by existing literature.